PENGARUH PERINGKAT OBLIGASI, TINGKAT SUKU BUNGA SERTIFIKAT BANK INDONESIA, RASIO LEVERAGE, UKURAN PERUSAHAAN, UMUR OBLIGASI, DAN TINGKAT INFLASI PADA IMBAL HASIL OBLIGASI KORPORASI DI BURSA EFEK INDONESIA (Studi pada semua obligasi korporasi di BEI periode tahun 2012-2014) - Puput Purwanti; Wida Purwidianti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This research was aimed at analyzing the effect among bong rating, interest rate of Bank Indonesia certificate, leverage ratio, firm size, maturity, and inflation yield on corporate bonds. Yield to reseive from bond return always show fluctuation of moves. Therefore, follow up research was needed to do to use how significant the effect of the variables. The population used in this research was all companies disclosing bonds listed in Indonesia Stock Exchange 2012-2014. There were 67 bond of 35 companies as sample in this research. The data analysis used in research was multiple regression analysis. The result of this research showed that obligation rank, debt to equity ratio, and inflation had negative and significant effect on bond yield, that interest rate of Bank Indonesia Certificate had positive and significant effect on bond yield, firm size had negatif and insignificant effect on bond yield, maturity had positive and insignificant effect on bond yield. Keywords: bond yield, bond rate, interest rate, leverage ratio, firm size, maturity and inflattion.